Legal Protection of Notary Employees As Instrumental Witnesses In The Making of Notary Deeds - Hais Subaga Athazada; Nuzulia Kumala Sari; Iwan Rachmad Soetijono (Journal of Law, Politic and Humanities, 2026)
The existence of notaries as public officials plays an important role in the drafting of authentic deeds, which function as perfect legal evidence in legal relationships within society. In the process of drafting authentic deeds, the presence of instrumental witnesses constitutes a formal requirement that must be fulfilled to maintain the authenticity of the deed. In notarial practice, instrumental witnesses are generally notary employees because they are considered to understand the procedures and technical aspects of deed Preparation. Problems arise when disputes concerning notary deeds occur, while legal protection for notary employees acting as instrumental witnesses have not been explicitly regulated under the Law on Notarial Office. This study aims to analyze the legal protection of notary employees acting as instrumental witnesses, the limits of their legal liability, and future legal arrangements regarding such protection. This research employs a normative legal method using statutory , conceptual , and case approaches. The results of the study indicates that the absence of explicit legal regulation concerning the protection of instrumental witnesses creates legal uncertainty in notarial practice. The legal responsibility of notary employees acting as instrumental witnesses is principally limited to formal aspects of deed execution rather than the substantive content of the deed. Therefore, a more comprehensive legal reform is necessary to provide legal certainty and protection for notary employees acting as instrumental witnesses.